Ethanol toxicity in pancreatic acinar cells: Mediation by nonoxidative fatty acid metabolites - Criddle, David N. (National Academy of Sciences, 2004)
Ethanol causes pancreatic damage by an unknown mechanism. Previously, we demonstrated that a sustained rise of the cytosolic Ca(2+) concentration ([Ca(2+)](i)) causes pancreatic acinar cell injury. Here we have investigated the effects of ethanol and its metabolites on Ca(2+) signaling in pancreatic acinar cells. Most cells exposed to ethanol (up to 850 mM) showed little or no increase in [Ca(2+)](i) (and never at concentrations <50 mM). During sustained exposure to 850 mM ethanol, acetylcholine (ACh) evoked a normal [Ca(2+)](i) elevation and following ACh removal there was a normal and rapid recovery to a low resting level. The oxidative metabolite acetaldehyde (up to 5 mM) had no effect, whereas the nonoxidative unsaturated metabolite palmitoleic acid ethyl ester (10–100 μM, added on top of 850 mM ethanol) induced sustained, concentration-dependent increases in [Ca(2+)](i) that were acutely dependent on external Ca(2+) and caused cell death. These actions were shared by the unsaturated metabolite arachidonic acid ethyl ester, the saturated equivalents palmitic and arachidic acid ethyl esters, and the fatty acid palmitoleic acid. In the absence of external Ca(2+), releasing all Ca(2+) from the endoplasmic reticulum by ACh (10 μM) or the specific Ca(2+) pump inhibitor thapsigargin (2 μM) prevented such Ca(2+) signal generation. We conclude that nonoxidative fatty acid metabolites, rather than ethanol itself, are responsible for the marked elevations of [Ca(2+)](i) that mediate toxicity in the pancreatic acinar cell and that these compounds act primarily by releasing Ca(2+) from the endoplasmic reticulum.